Coup d'etat - Turtledove, Harry (Turtledove, Harry. War that came early, 2012)
In the story of an alternate World War II that considers what might have happened if Chamberlain had chosen not to appease Hitler, the Germans fight with England and France to defeat Russia, while the United States struggles in a war against Japan.